Feasibility of Solar Updraft Towers as Photocatalytic Reactors for Removal of Atmospheric Methane–The Role of Catalysts and Rate Limiting Steps - Huang, Yanfang; Shao, Yimin; Bai, Yang; Yuan, Qingchun; Ming, Tingzhen; Davies, Philip; Lu, Xiaohua; de Richter, Renaud; Li, Wei (Frontiers in Chemistry, 2021)
Due to the alarming speed of global warming, greenhouse gas removal from atmosphere will be absolutely necessary in the coming decades. Methane is the second most harmful greenhouse gas in the atmosphere. There is an emerging technology proposed to incorporating photocatalysis with solar updraft Towers (SUT) to remove methane from the air at a planetary scale. In this study, we present a deep analysis by calculating the potential of methane removal in relation to the dimensions and configuration of SUT using different photocatalysts. The analysis shows that the methane removal rate increases with the SUT dimensions and can be enhanced by changing the configuration design. More importantly, the low methane removal rate on conventional TiO2 photocatalyst can be significantly improved to, for example, 42.5% on a more effective Ag-doped ZnO photocatalyst in a 200 MW SUT while the photocatalytic reaction is the rate limiting step. The factors that may further affect the removal of methane, such as more efficient photocatalysts, night operation and reaction zone are discussed as possible solutions to further improve the system.